Effect of Cold Plasma Treatment on Physical Properties of Multilayer Plastics for Polymer Asphalt Applications - Dimas Agung Setiaji; Mochamad Chalid; Tomy Abuzairi; Maurice Efroza; Adam Febriyanto Nugraha (Piston: Journal of Technical Engineering, 2022)
Multilayer plastic waste continues to increase due to the ever-growing consumption and needs of the global citizen and is one of the most challenging types of waste to recycling because of its nature. The accumulation and indiscriminate disposal of waste can pose a potential risk of environmental problems. A solution that can be implemented is to mix bitumen and waste polymer as asphalt manufacturing. Despite its advancement in research, many potential parameters are still to be discovered to achieve optimal results. Through cold plasma treatment, a surface treatment may occur at the multilayer polypropylene that causes the change from hydrophobic to hydrophilic properties. Treating the polymer with cold plasma will provide good hydrophilic properties without changing the overall chemical and thermal properties of the sample. This will result in an alternative aggregate for the bitumen for asphalt manufacturing. Bitumen coupled with the addition of plastic still provides an optimal hardness and ductility, meanwhile having a more economically viable manufacturing process than other processes.